PENGARUH METODE PEMBELAJARAN STORYTELLING TERHADAP KEMAMPUAN MENCERITAKAN TEKS HIKAYAT SISWA KELAS X SMA NEGERI 3 LENGAYANG - Selvi; Zulfitriyani; Upit Yulianti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
ABSTRACTThis research is motivated by the low ability of students in retelling fable texts,especially related to the mastery of linguistic and non-linguistic factors whenspeaking in front of the class. One of the learning methods that is consideredcapable of improving these skills is the storytelling method, because it emphasizesstorytelling activities in an interesting and communicative manner. The purpose ofthis study is to describe the ability to retell fable texts before and after theapplication of the storytelling learning method and to determine the effect of themethod on the ability to retell fable texts of class X students of SMA Negeri 3Lengayang. This study uses a quantitative method with a pre-experimental designthrough one group pretest-posttest design. The research sample was 30 class Xstudents of phase E7 who were selected based on the lowest average score fromseven classes. The research data were obtained through oral tests before andafter treatment, then analyzed using normality tests, homogeneity tests, and ttests. The results showed that the average ability to retell fable texts of studentsbefore using the storytelling method was in the sufficient category with an averagescore of 60.61. After implementing the storytelling method, students' abilitiesimproved significantly, with an average score of 79.00, falling into the goodcategory. The t-test results showed a calculated t value of 10.85, greater than thet-table value of 1.70 at a significance level of 0.05. This indicates that thestorytelling learning method has a positive effect on students' ability to tell fabletexts.Keywords: storytelling, storytelling ability, fable texts, Indonesian languagelearning